Truly Teaming : Partnering to Integrate Gender in Kenya’s Water Sector - Torkelsson, Asa; Rop, Rosemary; Wasike, Theresa (World Bank, Washington, DC, 2012)
In spite of its importance in development and poverty reduction, the water sector has had one of the largest gaps between what women do and the influence they actually have. In Kenya, women are still underrepresented in water governance structures at all levels, yet they are the most negatively affected by unavailability of water. To substantially boost gender integration in the country's water sector, a team of professionals from the World Bank, the Water and Sanitation Program (WSP), and the Ministry of Water and Irrigation (MoWI) pooled their resources and energies. This smart lesson illustrates how forging nurturing partnerships with a wide variety of development partners can result in effective strategies for gender mainstreaming allowing us to do far more together than any one of us could do alone.